Resolution of the III International menopause expert forum - - (Publishing House TRILIST, 2022)
The III International Menopause Expert Forum took place on November 24, 2021. The working group of the expert council included leading experts in endocrine gynaecology from Belarus, Armenia, Georgia, Kazakhstan, Kyrgyzstan, Uzbekistan, and Ukraine. To date, menopause hormone therapy (MHT) initiated during the "therapeutic window of opportunity" has proved to have a protective effect against various age-associated diseases. Despite this, the percentage of women using MHT remains low and, for example, in Ukraine and Kazakhstan, equals nearly 2%. However, only one in four of these women have been using MHT for more than a year. The main reasons for such low percentage of women using MHT are as follows: 1. Low patient adherence to MHT (due to misunderstanding of the menopause factors, menopause symptoms, treatments, hormonophobia, poor communication with healthcare professionals etc.). 2. Healthcare professional's vigilance due to the possible risks associated with MHT (breast cancer, venous thromboembolism, cardiovascular diseases etc.). 3. Healthcare professionals face difficulties during the MHT prescription or subsequent patient management (unplanned haemorrhages, concomitant pathologies in a woman, i.e. fibroids, varicose veins, arterial hypertension etc.). Aiming to improve medical care for menopausal women, experts attending the Forum focused on the latest data on the risks of breast cancer and venous thromboembolism, MHT effect on the risk of coronary heart disease and arterial hypertension, the potential of prescribing MHT to patients with uterine myoma and on increasing treatment adherence.